2020
DOI: 10.1088/1361-6641/ab8539
|View full text |Cite
|
Sign up to set email alerts
|

High-quality nanodisk of InGaN/GaN MQWs fabricated by neutral-beam-etching and GaN regrowth: towards directional micro-LED in top-down structure

Abstract: A nanodisk array of blue InGaN/GaN multiple quantum wells was made using neutral beam etching (NBE) followed by GaN regrowth. The NBE-fabricated nanodisk presented a vertical and highly smooth sidewall surface where the InGaN well layers were easily distinguished even with a scanning electron microscope. A high interface quality without any voids or obvious defects was obtained between the nanodisk and the regrown-GaN layer. The nanodisk after regrowth presented a smaller blueshift of photoluminescence emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…On the other hand, R-value of NBE was significantly less than that of Cl 2 plasma etching (210%) as compared with the previous report [37]. Previous studies on using Cl 2 NBE for fabricating μLED reported that the surfaces recovered after GaN regrowth [15] and the EQE was stable at low current density (1 A cm −2 ) [14]. Thus, our results prospected that the etching interface of HI NBE can recover as well or better than that of Cl 2 NBE because it does not have any etching residue.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…On the other hand, R-value of NBE was significantly less than that of Cl 2 plasma etching (210%) as compared with the previous report [37]. Previous studies on using Cl 2 NBE for fabricating μLED reported that the surfaces recovered after GaN regrowth [15] and the EQE was stable at low current density (1 A cm −2 ) [14]. Thus, our results prospected that the etching interface of HI NBE can recover as well or better than that of Cl 2 NBE because it does not have any etching residue.…”
Section: Resultscontrasting
confidence: 56%
“…Etching 15%-indium-content InGaN/GaN MQW blueemitting (≈440 nm) μLEDs with chlorine gas has a low etching rate due to the InGaN layer (4.5 nm min −1 for GaN and 2 nm min −1 for In 0.15 GaN) [14] and forms indium residue [15]. This etching residue comes from low-volatility indium chloride remaining on the surface, and it causes recombination centers and disturbs the regrowth process [15]. Moreover, if red-light-emitting μLEDs are to be etched, the indium content ratio increases from 15% to 35%.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the top-down approach is that it offers more flexibility in creating arrays of nanowires with different shapes, dimensions, and densities on a wafer scale. However, plasma patterning is known to cause damage and rough surfaces, which prevent high-quality surface regrowth [21,22] while the regrowth of the quantum wells on the nanowire sidewalls for core/shell emitting structures is favored if m-oriented facets are present. One of the greatest challenges in patterning high aspect ratio GaN nanowires is achieving high GaN-tomask etch selectivity while maintaining high-quality etched surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies addressing this etch selectivity issue use Ni-based hard masks obtained by lift-off lithography, since they offer high selectivity for deep GaN etching (>15) [16][17][18]23]. However, for certain applications, the use of metal masks may not be desired due to potential contamination and hard mask roughness issues [22]. For industrial applications, the use of dielectric masks is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because GaN has a refractive index of 2.35, which is higher than that of air, the escape cone angle of GaN-based LEDs is approximately 25.18°, as determined using Snell’s law. , GaN-based LEDs are expected to show a light extraction efficiency (LEE) of up to a few percent. Thus, the light escape cone angle of the disk-type LEDs prepared using the dry-etching process can be increased by using a cylindrical shape that can emit light at all angles because of the light emission direction perpendicular to the surface. However, during the fabrication of a disk-type LED structure, the dry-etching process can produce major crystal defects, which act as nonradiative recombination centers and significantly decrease the internal quantum efficiency of the LED structure despite the increase in its LEE. , In particular, the emission efficiency of an LED decreases significantly with a decrease in its size because of the presence of dry-etched sidewall defects in it. , However, because semipolar GaN films can be etched by chemical etchants, semipolar GaN-based microdisk (MD)-type LEDs fabricated via wet etching are expected to exhibit improved LEE without substantial dry-etching damage for applications in micro-LED display light sources. This is because, in the wet-etching process, the semipolar GaN film is etched by a chemical etchant to avoid dry-etching damage .…”
Section: Introductionmentioning
confidence: 99%